Journals - Scott, Robert Falcon (Oxford University Press, 2005)
In January 1912, Britain's Captain Robert F. Scott reached the South Pole, only to find he had been beaten by Roald Amundsen's Norwegian expedition. Scott and his companions faced an 850-mile march to safety. All perished on the return. A few months later, a search party found Scott's body and the journals that told his tragic story.